2015
DOI: 10.1111/papr.12296
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Ganglion Block for Painful Congenital Venous Malformation of the Arm

Abstract: Stellate ganglion block is an established intervention used in pain management settings. Its use in the treatment of congenital venous malformations (VM) of the upper limb has never been described. We present a case of ultrasound-guided stellate ganglion block for a patient who derived excellent relief from pain uncontrolled with conservative and pharmacological methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…2 Most previously reported cases were diagnosed after 2 years of age, with the exception of two neonatal cases of Klippel-Trenaunay syndrome. 2,6,7 In contrast, in our case, VM was obvious at birth owing to its large size, despite the lack of signs of Klippel-Trenaunay syndrome.…”
Section: Discussioncontrasting
confidence: 83%
“…2 Most previously reported cases were diagnosed after 2 years of age, with the exception of two neonatal cases of Klippel-Trenaunay syndrome. 2,6,7 In contrast, in our case, VM was obvious at birth owing to its large size, despite the lack of signs of Klippel-Trenaunay syndrome.…”
Section: Discussioncontrasting
confidence: 83%
“…Its indications are wide, ranging from Raynaud disease, hot flashes to a series of pain conditions such as complex regional pain syndrome, atypical facial pain, and upper extremity pain. [ 7 ] Although the mechanisms underlying the effect of stellate ganglion block on various pathologies is not completely understood, it is conceivable and plausible that wide indication implies wide ranges of mechanisms as sympathetic nervous system is interconnected throughout the whole body.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently a meta-analysis concluded that SGB improved postoperative gastrointestinal function recovery in surgical patients who underwent general anesthetics. [ 61 ] Case reports have also identified a positive benefit from SGB in the treatment of upper limb erythromelalgia,[ 62 ] upper limb ischemia,[ 63 64 ] pain from vasculitis,[ 65 ] painful congenital venous malformations of the arm,[ 66 ] persistent hiccups,[ 67 ] thalamic pain,[ 68 ] central post-stroke pain,[ 69 ] abducens palsy,[ 70 ] palmar hyperhidrosis,[ 71 ] refractory migraine,[ 72 ] refractory tension headache[ 73 ] and various types of orofacial pain. [ 74 75 ]…”
Section: Reviewmentioning
confidence: 99%